1982
DOI: 10.1002/cne.902110304
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem projections of sensory and motor components of the vagus nerve in the rat

Abstract: The sensory and motor connections of the cervical vagus nerves and of its inferior ganglion (nodose ganglion) have been traced in the medulla and upper cervical spinal cord of 16 male Wistar rats by using horseradish peroxidase (HRP) neurohistochemistry. The use of tetramethyl benzidine (TMB) as the substrate for HRP permitted the visualization of transganglionic and retrograde transport in sensory nerve terminals and perikarya, respectively. The vagus nerve in the rat enters the medulla in numerous fascicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
290
4
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(314 citation statements)
references
References 18 publications
19
290
4
1
Order By: Relevance
“…However, we do not feel that this is the case because contralateral vagal afferents also terminate in the area of the mNTS (14,20).…”
Section: Experimental Protocolsmentioning
confidence: 87%
“…However, we do not feel that this is the case because contralateral vagal afferents also terminate in the area of the mNTS (14,20).…”
Section: Experimental Protocolsmentioning
confidence: 87%
“…The implications of this may be important for understanding how putative vagovagal reflexes are organized within the DVC. Afferents from the stomach tend to localize to the dorsomedial NTS, whereas baroreceptor input is concentrated in the medial NTS, respiratory sensation in the ventrolateral NTS, and pharyngeal sensation in the intermediate NTS [1,14]. Dendrites from any area might impinge on another area, so focal glutamate release-either from vagal afferent terminals or after glutamate photoactivation-might activate cells residing in another anatomical subdivision of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Though VNS failed to show acute modifications following on and off periods of activation (Salinski and Burchiel, 1993), experimental evidences have suggested that electrical stimulation induced modification of brain rhythms via the nucleus tractus solitarius (NTS), which is the main site of visceral afferent complex termination and is regulated by cholinergic inputs (Beckstead and Norgren, 1979;Kalia and Sullivan, 1982;Rutecki, 1990;Schacther and Saper, 1998). However, the extended network of NTS connections (Saper, 1995) might mediate the biochemical and electrical effects of VNS through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the therapeutic action of VNS remains unclear, however. Although its efficacy has been suggested to result from complex interactions of biochemical and electrical events (Beckstead and Norgren, 1979;Kalia and Sullivan, 1982;Rutecki, 1990), few studies have examined the effects of VNS on the EEG. …”
Section: Introductionmentioning
confidence: 99%